RELATIONSHIPS OF THE VOCATIONAL POWER WITH THE ABILITY TO SPEAK - Wulan Anggraeni, Sri; Alpian, Yayan; Sukmawati, Fitri (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to determine the relationship between vocabulary mastery with students’ speaking abilities. The research method uses a quantitative descriptive approach using correlation research techniques. The research design used in this study is the One-Shot Case Study design. The subjects in this study were fifth grade elementary schools with a total of 112 students. Validity test is calculated using the Product Moment formula and reliability is tested by the Cronbach Alpha formula. The data analysis technique used is descriptive statistical analysis. Hypothesis testing uses correlation analysis with the Pearson Product Moment formula. The results showed that there was a significant relationship between the mastery of vocabulary with the ability to speak, as indicated by the calculated value of 0.708 greater than the table of 0.185. It can be concluded that the mastery of vocabulary with the ability to speak has a positive and significant relationship. This study is recommended to teachers to introduce various Indonesian vocabulary words to students, so that students’ mastery of Indonesian vocabulary is increased which can then make it easier for students to choose the words to be spoken.